An encyclopedia of swearing the social history of oaths, profanity, foul language, and ethnic slurs in the English-speaking world - Hughes, Geoffrey 1939-; Gale Group (Armonk, N.Y. M.E. Sharpe, 2006)
"Entries cover the full range of swearing and foul language in English, including details on the history and origins of each term and the social context in which it found expression. Categories include blasphemy, obscenity, profanity, the categorization of women and races, and modal varieties, such as the ritual insults of Renaissance "flyting" and modern "sounding" or "playing the dozens"."--Publisher's description.
Electronic reproduction.
Keywords: English language -- Obscene words -- Dictionaries; English language -- Slang -- Dictionaries; Blessing and cursing -- Dictionaries; Invective -- Dictionaries; Swearing -- Dictionaries; Electronic books